Bicyclic peptide-enhanced covalent inhibitor of SARS-CoV-2 3CL protease - Qian Wang; Yanhui Wang; Jian Li; Hong Liu; Shiyu Chen (Exploration of Drug Science)
Aim: Develop technology to apply bicyclic peptides for discovering covalent inhibitors of proteases and use this technology to create bicyclic peptide—warhead conjugates for targeting the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 3C-like (3CL) protease. Enhance the potency of the discovered bicyclic peptides for potential development into anti-SARS-CoV-2 drugs. Methods: Rational design was employed to discover the initial bicyclic peptide—warhead conjugates. Medicinal chemistry optimization was conducted to improve the potency of these peptides. Enzymatic assays and mass spectrometry characterization were performed to validate the covalent inhibition of the target protease. Results: The need for peptide display selection in discovering hit bicyclic peptides was overcome. Active bicyclic peptide—vinyl sulfone inhibitors with nanomolar potency were discovered. Optimization through medicinal chemistry strategies not only improved the potency of the peptides but also revealed residue preferences at individual positions of the bicyclic peptide inhibitors. The most potent bicyclic peptide can inhibit the target with a half-maximal inhibitory concentration (IC50) of 40.46 ± 6.35 nM. Mass spectrometry tests confirmed the covalent inhibition of the target protease by the developed peptides. Conclusions: Bicyclic peptide and vinyl sulfone conjugates are a form of covalent and potent inhibitors for targeting proteases. The rational design of bicyclic peptide ligands is feasible when structural and amino acid preference information is available. Structural information is also crucial for optimizing the potency of bicyclic peptide ligands.